Modern weapons and military equipment for Issue 3/2014 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Israel launches new spy satellite;Production standard AH-6i completed the first flight;Sikorsky took demonstration optionally unmanned helicopter based on the Black Hawk;The successful launch of the new Indian air-to-air missile Astra aircraft Su-30MKI; The prototype of the new Japanese fighter planes take off this year;First flight of MC-27J gunship;An-70 passed the Ukrainian state tests;Iran unveils new air defence missile system;U.S. Navy to equip UAV MQ-8C for electronic warfare;Saab successfully completed testing of a new IRST's the Gripen E;Stealth of the F-35 - one more betrayed expectation.